Risk or License? Precautionary Principle’s Transition in Genetically Modified Organisms’ Benefits After Job Creation Law - Natamiharja, Rudi; Melati Davey, Orima; Sabatira, Febryani; Rakhma Banjarani, Desia; Wierma Putri, Ria (Udayana Journal of Law and Culture; Vol 6 No 2 (2022), 2022)
This article aims to discuss the implementation of precautionary principle on the use of Genetically Modified Organisms (GMO) in Indonesia as well as to identify and evaluate the changes of provisions on precautionary principles related to the use of GMOs as stipulated in the Environmental Law and the later Job Creation Law in Indonesia. This article employs normative legal research that descriptively examines humans, circumstances, and other phenomena to strengthen old theories and support new theories that are still in the drafting stage. It uses secondary data sources consisting of primary legal materials and secondary legal materials. The result shows that the implementation of precautionary principle on the use of GMOs is based on the Environmental Law and the Job Creation Law which can be seen in the AMDAL. Under the Environmental Law, the implementation of precautionary principle prioritizes the importance of a risk's impact before the activity is carried out. Whereas in the Job Creation Law, the operation of an activity adjusts the level of risk, namely low, medium, and high. Hence, based on Job Creation Law, a business activity that already utilizes GMOs is allowed to conduct its operation if the risk is assessed as low. It is due to a transition between the risk approach in the Environmental Law and the licensing approach in the Job Creation Law. This article suggests that in GMO usage, the government should find more specific precautionary implementation than regulations and labels since regulations alone are too abstract to comprehend in a society.